TEFROESTRATIGRAFÍA (40 000-2000 a.P.) EN EL SECTOR CARIBE DE LOS VOLCANES BARVA, CONGO Y HULE, CORDILLERA CENTRAL, COSTA RICA - Alvarado, Guillermo E. (2011)
The area is located in the north side of the Central Volcanic Range, near the Poás (historicallyactive), Von Frantzius (active at least 40 000 years B.P.) and Congo (active about 6000 years B.P.) volcanoes. Itcomprises the Hule maar that exploded 2800 years ago and possibly showed some minor eruptive periods about1700 and 670 years B.P., and the Barva volcano. Pumice sheets (airfall and flow) which crop out in both margins of the Sarapiquí river are older than 40 000 years. Field survey showed the existence of thick pyroclasticsheets (phreatomagmatic tuffs and plinian lapilli) from the Congo and Hule volcanoes. Among the facies associated with Congo we identified airfall facies of andesitic composition and corresponding to different eruptions (C1 y C2); pumice and less frequent-block and ash pyroclastic flow facies and a lahar facies with a radiocarbon age of 6030 years. Within the explosive event related with the Hule volcanic center, besides the plinian airfall facies, there are stratified tuffs and lapilli deposits corresponding to base surges and ash cloud surges.